Perancangan Sistem Gerak Kamera Laba-laba dengan Metode Kinematika Balik - Muhammad Aziz Muslim; Frido Wahyu Alifantio (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2019)
Spider camera (spidercam) is a camera equipped with a movement system that resembles the movement of a spider. The camera can move in a three-dimensional field by pulling and stretching the rope or cables arranged in a certain configuration. This study proposed the use of an inverse kinematic to control the movement of the camera. This method is seeking the relationship between the desired coordinates with the angle that must be moved from each motor that composes it. To move the motor, an analytically tuned PID controller is employed. Experimental results show that using the proposed system, the camera is successfully placed in accordance with the desired position with 100% accuracy. From motor response side, however, the system's performance still needs to be improved so that a smoother movement can be obtained.